2022
DOI: 10.3390/ijerph192214681
|View full text |Cite
|
Sign up to set email alerts
|

The Link between the Demographic and Clinical Factors and Fatigue Symptoms among Rheumatoid Arthritis Patients

Abstract: Rheumatoid arthritis (RA) is a chronic systemic disease of connective tissue with periods of exacerbation and remission. Fatigue is excessive strain throughout the body that is disproportionate or unrelated to an activity or lifestyle. Fatigue is an integral part of RA in most patients. The study aimed to assess the level of fatigue in RA patients and establish the relationship between fatigue and demographic and clinical factors. The study group consisted of 128 RA patients according to European League Agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…RA patients with high disease activity might have additional joint pain and elevated inflammation, which caused severe fatigue. 6,31,38 (3) Our study used BRAF-MDQ and BFI-C scales to assess fatigue, which was different from scales used in other previous studies. 6,9,32 Moreover, differences in the included population between our study and other previous studies might cause different results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RA patients with high disease activity might have additional joint pain and elevated inflammation, which caused severe fatigue. 6,31,38 (3) Our study used BRAF-MDQ and BFI-C scales to assess fatigue, which was different from scales used in other previous studies. 6,9,32 Moreover, differences in the included population between our study and other previous studies might cause different results.…”
Section: Discussionmentioning
confidence: 99%
“…32 Furthermore, one study finds that pain, morning stiffness, hemoglobin, joint tenderness, and disease activity are associated with fatigue in RA patients. 6 Another study exhibits that age, education, hypertension, disease activity, and other factors are correlated with fatigue in RA patients. 9 Our study found that education level and disease activity were independent risk factors of fatigue reflected by the BRAF-MDQ and BFI-C scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study group consisted of 128 patients hospitalized in Poznan's rheumatology departments (the Rheumatology Ward of the M. Dega Orthopedic and Rehabilitation Clinical Hospital of Poznan University of Medical Sciences and the Józef Struś Poznan Multidisciplinary City Hospital) from December 2016 to January 2018, see [12]. The main criterion for inclusion in the study was a diagnosis of RA according to the American College of Rheumatology (ACR) criteria and the European League Against Rheumatism (EULAR) from 2010 [13].…”
Section: Study Design and Studied Subjectsmentioning
confidence: 99%
“…A score ≥ 11 in each of the subscales indicates a positive case. Pain was evaluated using the visual analog scale, ranging from 0 (no pain) to 10 (maximum pain), quality of life using the 36-item Short Form Survey (SF-36) [49], physical functioning using the Health Assessment Questionnaire (HAQ) [50], and fatigue using the Functional Assessment of Chronic Illness Therapy-Fatigue scale (FACIT) [51]. The score on the FACIT questionnaire ranges from 0 to 52 points, with higher values indicating lower degrees of fatigue.…”
Section: Study Protocolmentioning
confidence: 99%